2017
DOI: 10.1111/lam.12736
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages as indicators of faecal pollution and enteric virus removal

Abstract: Significance and Impact of the Study: Bacteriophage are alternative fecal indicators that may be better surrogates for viral pathogens than fecal indicator bacteria (FIB). This report offers a summary of the existing literature concerning the utility of bacteriophage as indicators of viral presence (fecal sources and surface waters) and persistence (in built infrastructure and aquatic environments). Our findings indicate that bacteriophage levels in all matrices examined are consistently lower than FIB, but si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 170 publications
7
109
0
9
Order By: Relevance
“…The total log reductions in enteric viruses over the entire course of the treatment process were more similar to the 2–3 log reduction seen for infectious coliphage indicators than the 3–4 log reduction seen for cultured fecal indicator bacteria, similar to findings described in Dias, Ebdon, and Taylor (), McMinn, Ashbolt, et al. (), Hata et al. (), and Rose et al.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The total log reductions in enteric viruses over the entire course of the treatment process were more similar to the 2–3 log reduction seen for infectious coliphage indicators than the 3–4 log reduction seen for cultured fecal indicator bacteria, similar to findings described in Dias, Ebdon, and Taylor (), McMinn, Ashbolt, et al. (), Hata et al. (), and Rose et al.…”
Section: Resultssupporting
confidence: 85%
“…McMinn, Ashbolt, et al. () compared multiple WRRF studies and concluded that overall fecal indicator bacteria reductions (mean reductions were 2.38 ± 1.26 and 2.22 ± 1.61 for E. coli and enterococci, respectively) were greater than coliphages reductions (mean reductions were 1.46 ± 1.18 and 1.46 ± 1.24 for male‐specific and somatic coliphages, respectively). Pouillot et al.…”
Section: Resultsmentioning
confidence: 99%
“…The relationships between coliphages and human viruses as well as its relationship to health risk were assessed in several ANNUAL LITERATURE REVIEW studies with inconsistent results. Some researchers (Jofre et al, 2016) considered coliphages correlated with human viruses and health risk, while others (McMinn, Ashbolt, & Korajkic, 2017) declined the statement. McMinn et al (2017) considered Enterococci phages as potential fecal indicators, surviving in both fresh and marine water in tropical and subtropical regions.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…; McMinn et al . ) have been extensively studied for this purpose. Humans and animals excrete both groups.…”
Section: Introductionmentioning
confidence: 99%